Effects of administering exogenous bovine somatotropin to beef heifers during the first trimester on conceptus development as well as steroid- and eicosanoid-metabolizing enzymes. (15th February 2021) - Sanford, Carla D; Owen, Megan P T; Oosthuizen, Nicola; Fontes, Pedro L P; Vonnahme, Kimberly A; Nelson, Megan; Reyaz, Arshi; Lemley, Caleb O; DiLorenzo, Nicolas; Cliff Lamb, Graham
Abstract: The aim of this study was to evaluate the effect of bovine somatotropin (bST ) on fetal and placental development during the first third of gestation in beef heifers. Angus heifers ( n = 97) were randomly assigned to either receive a 500-mg injection of bST (BST ) biweekly on days 0, 15, 29, 43, and 57 of gestation or not receive bST (CTL ) throughout the experiment. Body weight (BW ) was assessed on days −9, −3, 0, 15, 22, 29, 43, 50, 57, 64, and 77, while blood samples were collected on days 0, 22, 50, and 64. Pregnancy status was determined via transrectal ultrasonography on days 29 and 64. A subset of pregnant heifers (BST, n = 7; CTL, n = 5) were harvested on day 84, and complete gravid reproductive tracts and liver tissue were collected for analysis. Cytochrome P450 1A ( CYP1A ), 2C ( CYP2C ), 3A ( CYP3A ), and uridine 5′-diphospho-glucuronosyltransferase (UGT ) activities were determined. Mean change in BW and average daily gain of heifers between fixed-time artificial insemination (day 0) and day 77 did not differ between treatments ( P ≥ 0.05). Mean concentrations of insulin-like growth factor 1 (IGF -1) were greater ( P < 0.001) in BST (347 ± 27.7 ng/mL) compared with CTL (135 ± 32.8 ng/mL) heifers. Mean placental weight, fetal membrane weight, uterine weight, and ovarian and corpus luteum (CL ) weights, as well as fetal morphometric data, did not differ ( P ≥ 0.05) between treatments. However, BST heifers had greater ( P = 0.03) quantities of combined fetal fluid compared with CTL (521.6 ± 22.9 vs. 429.6 ± 27.14 g, respectively). Tendencies were observed for BST heifers to have reproductive tracts with fewer placentomes ( P = 0.08) and fetuses with greater umbilical diameters ( P = 0.09) compared with CTL. The activity of CYP1A did not differ ( P ≥ 0.05) within the maternal and fetal liver, caruncle, cotyledon, or CL tissue samples between treatments. Furthermore, CYP3A activity was only observed in maternal liver samples and was not different between treatments ( P ≥ 0.05). Interestingly, CYP2C activity was greater ( P = 0.01) in the liver of BST vs. CTL heifers, and UGT activity was greater ( P = 0.02) in the CL from BST heifers compared with CTL. In conclusion, the administration of bST during the first third of gestation increased plasma concentrations of IGF-1, which resulted in an increase in fetal fluid, decrease in placentome number, and greater umbilical diameter, but failed to alter fetal development.